2019
DOI: 10.3389/fevo.2019.00376
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to High Concentrations of Road Salt Decreases the Immune Response of Dragonfly Larvae

Abstract: Salinization of freshwater ecosystems, due to the application of road salts, is recognized as a potential threat to aquatic communities. Much of the research on the impact of salinity has focused on performance metrics in vertebrates, including respiration and osmoregulation. Here we focus on immune function in larvae of the dragonfly Anax junius, a top predator in fishless aquatic habitats. Impacts on this top predator have the potential to cascade through the community, and immune function is known to be bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 55 publications
2
17
0
1
Order By: Relevance
“…Importantly, some common second intermediate hosts of freshwater trematodes have been shown to exhibit increased susceptibility to infection when exposed to similar salt concentrations (e.g. Buss & Hua, 2018; Mangahas et al ., 2019), setting up a possible mismatch in host vs. parasite effects when road salts contaminate natural habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, some common second intermediate hosts of freshwater trematodes have been shown to exhibit increased susceptibility to infection when exposed to similar salt concentrations (e.g. Buss & Hua, 2018; Mangahas et al ., 2019), setting up a possible mismatch in host vs. parasite effects when road salts contaminate natural habitats.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) found that wood frog tadpoles exposed to 600 or 1050 mg NaCl/l not only had higher intensities of infection by trematode parasites, but also exhibited reduced anti-parasite behaviour in these conditions. Buss & Hua (2018) similarly reported that trematode parasitism in larval wood frogs increased by 68% at concentrations of 1000 mg/l of NaCl or more (note: NaCl concentrations throughout are converted to mg/l if originally reported in other units), and larval dragonflies exhibited a reduced immune response to simulated parasite challenge when subjected to chronic NaCl exposure at 3000 mg/l (Mangahas et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mangahas et al . ); immunosuppression in response to chronic predation risk appears to be a common, but not universal, response that arises from trade‐offs and from a physiological network of stress and immune responses (Adamo et al ., ; Adamo, ). By contrast, the present study exposes larvae over a relatively limited time period (72 hours) making this an acute, rather than chronic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Such energy investment for coping with osmotic stress in saline waters might be to some extent compensated for by the lower predation and interspecific competition occurring in these media (Arribas et al, 2019;Herbst, 2001;Southwood, 1988). All aspects of the insect immune response also are metabolically costly, which may result in energetic trade-offs between different processes (Adamo et al, 2008;Ardia et al, 2012;Lazzaro & Little, 2009;Rantala & Roff, 2005), such as osmoregulation (Mangahas et al, 2019), as well as opportunity costs (fitness loss if other tasks cannot be met) (Schmid-Hempel, 2005).…”
Section: Introductionmentioning
confidence: 99%